Tissue-dependent differences in the asynchronous appearance of mast cells in normal mice and in congenic mast cell-deficient mice after infusion of normal bone marrow cells - DU, T (Blackwell Science Inc, 1996)
The time courses of the appearance of tissue mast cells in six sites were compared in normal WBB6F(1)-+/+ mice (+/+) and in congenic mast cell-deficient WBB6F(1)-W/W(v) mice (W/W(v)) that received an intravenous infusion of bone marrow cells from +/+mice (BM→W/W(v)). As assessed by morphometric analysis of Carnoy's solution-fixed, methylene blue-stained tissue sections, the density of mast cells in the stomach mucosa, stomach submucosa, and spleen of +/+ mice reached maximal levels by 8 weeks of age, whereas the density of mast cells in the skin, extraparenchymal airway walls, and lung parenchyma did not reach maximal levels until 18 weeks of age. When 8-week-old W/W(v) mice were infused with 2×10(7) bone marrow cells from +/+ mice, mast cells appeared in the stomach mucosa and submucosa after 2.5 weeks, in the spleen and extraparenchymal airway walls after 5 weeks, and in the lung parenchyma after 10 weeks. Twenty weeks after bone marrow infusion, the mast cell densities in the spleen, stomach mucosa, and stomach submucosa were seven-, 13-, and five-fold greater, respectively, than those in age-matched +/+ mice, but were eight-, two-, and five-fold lower in the skin, extraparenchymal airway walls, and lung parenchyma, respectively. Thus, those tissues that in +/+ mice reached maximal mast cell densities earlier exhibited abnormally high mast cell densities in BM→W/W(v) mice, and those that reached maximal mast cell densities later in +/+ mice had abnormally low mast cell densities in BM→W/W(v) mice. Immunological and inflammatory responses are often compared in W/W(v) and BM→W/W(v) mice to assess mast cell dependency. Our results indicate that the capacity to restore a mast cell-dependent response in a particular tissue of the latter mice may relate to the local mast cell density and whether the immunological challenge activates mast cells only in that tissue or systematically with attendant widespread release of proinflammatory mediators.